APPLYING THE COMPASSIONATE LOVE FOR THE PASSION TO ACHIEVE TRANSFORMATION TOWARDS CREATIVE TOURISM OF CHAINAT PROVINCIAL ADMINISTRATIVE ORGANIZATION, THAILAND AFTER COVID-19 ENDEMIC - Senakhan, Thanuchart; PAVAPANUNKUL, Shayut (Asian Interdisciplinary and Sustainability Review, 2023)
The aim of this study is to present the results of applying compassionate love for passion to achieve transformation towards creative tourism concept framework. The conducted research used qualitative methods, especially literature on research methodologies is the mandate of the key engines of the results and discussion. It is the highlights of profound effect based on the way a research is designed and the outcome of revitalizing Thailand’s tourism sector to enable both policy at macro level (provincial) and at micro level (the firm) concept. This study objective was responses to served and designed the implications of the transformation to achieve creative tourism concept framework. With the mandate of the key engines of the results and discussion on revitalizing Thailand’s tourism sector to enable policy at macro level and at micro level concept. The study results and discussions to this case studies of Chainat Provincial Administrative Organization. It can be used by literature study of compassionate love for the passion to applying the transformations to achieve the conceptualization framework of creative tourism. Originally, this implications of the transformation towards compassionate love for the passion that influenced able strategy on culminates in a new positioning for a new opportunity that concerned to various benefits for creative tourism strategy on transforming tourism economy of Chainat Provincial Administrative Organization after COVID-19 endemic.